Serum Progesterone Levels as Predictor of Outcome in Severe Traumatic Brain Injury: Analysis of Cohort of 100 Patients - Chhiber, Sarbjit Singh; Gul, Adfer; Arif, Sajad; Wani, Abrar Ahad; Ramzan, Altaf Umar (Indian Journal of Neurosurgery, 2021)
Despite advances in research and improved neurological intensive care in recent years, the clinical outcome of severely head injured patients is still poor. Primary insult is followed by a complex cascade of molecular and biochemical events that lead to neuroinflammation, brain edema, and delayed neuronal death. No specific pharmacological therapy is currently available which prevents the development of secondary brain injuries, and most therapeutic strategies have failed in translation from bench to bedside. There are limitations of clinical and radiological methods in delineating the exact severity and prognosis of traumatic brain injury (TBI). A myriad complex biochemical markers are under investigation to delineate the extent of brain tissue damage and to independently predict the outcome, but a search for simple biomarker still eludes the research. Progesterone, a gonadal hormone and a neurosteroid, although controversial as a neuroprotective agent, may hold promise as a simple biochemical marker of the outcome in severe TBI.
Keywords: severe traumatic brain injury; progesterone; biochemical marker; outcome